Покращення екологічних показників колісного трактора використанням газового палива - Захарчук, О. В. (НТУ "ХПІ", 2014)
З використанням математичної моделі проведено теоретичні дослідження екологічних показників колісного трактора на основі експериментальних стендових досліджень газового двигуна. Експериментальними дослідженнями колісного трактора МТЗ-80 з газовим двигуном перевірена адекватність математичної моделі. Зроблено висновки, що застосування газового палива дозволяє значно покращити екологічні показники колісного трактора з переобладнаним з дизеля газовим двигуном.

compressed natural gas. With using of mathematical model was conducted a theoretica lresearch of environmental performance wheel tractor base don the experimental benchtests of the gasen gine. Experimental studies of wheeled tractor MTZ -80 with a gasen gine wastestedtheadequacy of mathematical models. In both series on the rules of UN/ECE R 49, which reflect the real operating conditions of the vehicle is achieved by reducing the to tale mission sin 1,96 times. Fuel consumptionandharm fule missions from engine exhaust gases calculate don a mathematical model for the motion of a wheel tractor MTZ-80 when the engine work son different fuels. It is concluded that the use of gas fuels can significantly improve the environmental performance of wheel tractor with a gasen gineretrofitted with diesel.
Improvement environmental performance wheel tractor using gas fuel
Keywords: математична модель; колісний трактор; газовий двигун; шкідливі викиди; mathematical model; wheeled tractor; gas engine; driving cycle; harmful emissions